Comparison Of Learning Outcome Geography Subject Matter Of History Of Earthquake Using Video Media And Powerpoint Media In Students Class X Sma Negeri 10 Kendari - Musyawarah, Rahma; Amaluddin, La Ode; Nursalam, La Ode (Universitas Negeri Makassar, 2017)
This study aims: 1) To know the significance of the difference between the average value of pre-test of experimental class students and the average value of pre-test of control class students, 2) Knowing the average value of post-test of experiment class students is significantly higher compared with the mean value of post-test control class, 3) Knowing the average value of students' gain of experimental class is significantly higher than the control group's average gain. This type of research is experimental research with pretest-posttest control group design. Sample determination technique is random sampling, obtained class X2 as experimental class and class X4 as control class. The data collection technique is done by giving the test of Geography learning result in the form of multiple choice test. Data analysis techniques use descriptive and inferential statistics. The results showed that the average value of post-test students class X2 = 79.67 with n-gain = 0.72 while class X4 = 75.05 with n-gain = 0.63. Based on t test analysis, t-Calculated = 2.07> tTable = 2.00 at a significant level of 95% (Î± = 0.05), this indicates that the average post-test grade of the experimental class is significantly higher than the the average value of post-test of control class students on the subject matter of the history of earth formation.